ANALISIS KRIMINOLOGI TINGGINYA ANGKA KECELAKAAN LALULINTAS DI WILAYAH HUKUM POLRES PESISIR SELATAN - Rafki, Muhammad (Universitas Ekasakti, 2020)
On the South Coast there is an increasing number of accidents every year. The criminological factor of the high number of traffic accidents in the Legal Area of the Pesisir Selatan Police is a factor of road conditions because Pesisir Selatan Regency has a geographical condition as a hilly plateau and is located along the southern coast of Sumatra. Another factor for community domesticated livestock is cows that are allowed to roam around without a leash. Efforts to Overcome Traffic Accidents in the Legal Area of the Pesisir Selatan District Police are carried out with several aspects, namely the engineering aspects of road maintenance and infrastructure, installation of markers, installation of warning lights (flip flop lights), installation of signs, and speed restrictions. The education aspect is carried out by improving motorist behavior, through appeals and training. Externally the obstacle faced is the lack of cooperation between the traffic police and other agencies related to traffic such as the transportation department and the nagari administration. The low level of legal awareness of road users in carrying out their work, namely driving their vehicles in accordance with good and correct driving operational standards, is often not applied by violating traffic regulations.